A phase 3 randomized, double-blind, placebo-controlled trial of ganitumab or placebo in combination with gemcitabine as first-line therapy for metastatic adenocarcinoma of the pancreas: the GAMMA trial - Fuchs, C S; Azevedo, S; Okusaka, T; Van Laethem, J-L; Lipton, L R; Riess, H; Szczylik, C; Moore, M J; Peeters, M; Bodoky, G; Ikeda, M; Melichar, B; et al. (Annals of oncology, 2015)
BACKGROUND: This double-blind, phase 3 study assessed the efficacy and safety of ganitumab combined with gemcitabine as first-line treatment of metastatic pancreatic cancer. PATIENTS AND METHODS: Patients with previously untreated metastatic pancreatic adenocarcinoma were randomly assigned 2 : 2 : 1 to receive intravenous gemcitabine 1000 mg/m(2) (days 1, 8, and 15 of each 28-day cycle) plus placebo, ganitumab 12 mg/kg, or ganitumab 20 mg/kg (days 1 and 15 of each cycle). The primary end point was overall survival (OS). Secondary end points included progression-free survival (PFS), safety, and efficacy by levels of circulating biomarkers. RESULTS: Overall, 322 patients were randomly assigned to placebo, 318 to ganitumab 12 mg/kg, and 160 to ganitumab 20 mg/kg. The study was stopped based on results from a preplanned futility analysis; the final results are reported. Median OS was 7.2 months [95% confidence interval (CI), 6.3-8.2] in the placebo arm, 7.0 months (95% CI, 6.2-8.5) in the ganitumab 12-mg/kg arm [hazard ratio (HR), 1.00; 95% CI, 0.82-1.21; P = 0.494], and 7.1 months (95% CI, 6.4-8.5) in the ganitumab 20-mg/kg arm (HR, 0.97; 95% CI, 0.76-1.23; P = 0.397). Median PFS was 3.7, 3.6 (HR, 1.00; 95% CI, 0.84-1.20; P = 0.520), and 3.7 months (HR, 0.97; 95% CI, 0.77-1.22; P = 0.403), respectively. No unexpected toxicity was observed with ganitumab plus gemcitabine. The circulating biomarkers assessed [insulin-like growth factor-1 (IGF-1), IGF-binding protein-2, and -3] were not associated with a treatment effect on OS or PFS by ganitumab. CONCLUSION: Ganitumab combined with gemcitabine had manageable toxicity but did not improve OS, compared with gemcitabine alone in unselected patients with metastatic pancreatic cancer. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov NCT01231347.
Keywords: Adenocarcinoma; deoxycytidin; proporcionální rizikové modely; nádory slinivky břišní; Humans; biomarker; Antimetabolites, Antineoplastic; lidé středního věku; Proportional Hazards Models; Disease Progression; Double-Blind Method; Biomarkers, Tumor; Drug Administration Schedule; gemcitabine; Antibodies, Monoclonal; Aged; Female; dospělí; protokoly protinádorové kombinované chemoterapie; pancreatic cancer; výsledek terapie; ganitumab; senioři; dvojitá slepá metoda; humanizované monoklonální protilátky; lidé; Gemcitabine; přežití bez známek nemoci; intravenózní podání; časové faktory; gemcitabin; nádorové biomarkery; Adult; Antibodies, Monoclonal, Humanized; IGF-1 receptor; ženské pohlaví; Kaplanův-Meierův odhad; Male; Pancreatic Neoplasms; Middle Aged; Deoxycytidine; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; protinádorové antimetabolity; Aged, 80 and over; monoklonální protilátky; Disease-Free Survival; senioři nad 80 let; progrese nemoci; adenokarcinom; Kaplan-Meier Estimate; mužské pohlaví; Administration, Intravenous; Time Factors; rozvrh dávkování léků